Individual Multilingualism of Students and Their Commitment to Learning German: A Pilot Study of the Faculty of Philology at Vilnius University - Diana Babušytė; Justina Daunorienė (Verbum, 2021)
The importance of promoting individual multilingualism is repeatedly emphasised worldwide in didactic, sociolinguistic and psycholinguistic studies. The prior knowledge of the learners and the networking of languages is pointed out in the Common European Framework of Reference for Languages. For this reason, the principles and methods of multilingual didactics play an important role in foreign language teaching due to their positive effects. Therefore, the question is increasingly being addressed how individual differences and progress of the learners regarding their linguistic backgrounds can be taken into account in language teaching. This article examines the question of whether and how Lithuanian university students see their multilingual repertoire as a resource for learning German. For this purpose, a survey was carried out among the Philology students of Vilnius University who study German as an optional course. The aim of this pilot study was to find out whether the students' previous knowledge of other languages helps them to learn German, or whether they see the influences of their mother tongue and other foreign languages as an obstacle that affects them negatively. The data obtained from the questionnaire presents the students' attitudes towards multilingualism, their multilingual skills and language awareness, as well as their language-related experience in acquiring German as a foreign language. The respondents' answers were processed using the method of the qualitative content analysis with a deductive-inductive approach. The results of the survey show that the majority of the students encountered the methods of multilingual didactics and see the multilingual competence as an important advantage for learning other foreign languages. Despite the language interference, the benefits of language skills outweigh the learning process. The students give examples based on their experience of how they use other languages for learning German and show well-developed metalinguistic awareness (e.g. language comparisons) and metacognitive skills (e.g. learning strategies). It is planned to continue this study by interviewing students from other faculties of Vilnius University (Medicine, Law, etc.) comparing their multilingual skills and metalinguistic awareness with the Philology students.